Monitoring the development of entrepreneurial activity of Ukrainian higher education institutions in the scientific field - Totska, Olesia Leontiivna (My University, 2024)
One of the main activities of Ukrainian higher education institutions (HEIs) is scientific. State HEIs can provide paid services, in particular in the field of scientific and scientific and technical activities. The purpose of this article is to monitor the development of the entrepreneurial activity of Ukrainian HEIs in the scientific sphere based on data on the volume of receipts to the special fund based on the results of scientific activity for 2018–2020 and to formulate proposals for stimulating such activity. In the course of the study, the ABC-analysis method was applied for the phased (2018, 2019, 2020) distribution of HEIs of Ukraine into three groups: A – HEIs with a large amount of income from scientific activity (about 80% of the total amount); B – HEIs with an average level of commercialization of the results of scientific activity (about 15%); C – HEIs with little or no income from scientific activities (about 5%). It was found that in the analyzed period, there was a gradual increase in the results of entrepreneurial activity in the scientific field of 138 Ukrainian state HEIs: revenues of HEIs first increased from UAH 363.688 million in 2018 to UAH 378.522 million in 2019, and then to UAH 460.455 million in 2020 It was noted that a significant share of these revenues (≈79–80%) was the receipts of approximately one-fifth of the HEIs: 19.57% in 2018, 18.84% in 2019, and 23.19% in 2020. The closest to the realization of the Pareto 20/80 principle was 2018, when the ratio of indicators of HEIs and their income was 20/79. It was found that in 2018–2020, 99 HEIs of Ukraine consistently fell into the same groups in terms of the amount of income to the special fund from scientific activities, 21 HEIs increased their positions (both smoothly and in leaps and bounds), 8 HEIs – on the contrary, decreased, and no trends were found for 10 HEIs. External and internal stimulation of the commercialization of scientific activity in HEIs of Ukraine is recommended.

Одним із основних видів діяльності українських закладів вищої освіти (ЗВО) є наукова. Державні ЗВО можуть надавати платні послуги, зокрема у сфері наукової та науково-технічної діяльності. Метою цієї статті є провести моніторинг розвитку підприємницької діяльності українських ЗВО у науковій сфері на основі даних про обсяги надходжень до спеціального фонду за результатами наукової діяльності за 2018–2020 рр. та сформувати пропозиції щодо стимулювання такої діяльності. У ході дослідження застосовано метод ABC-аналізу для поетапного (2018, 2019, 2020 рр.) розподілу ЗВО України на три групи: A – ЗВО з великим обсягом надходжень від наукової діяльності (близько 80 % у загальній сумі); B – ЗВО з середнім рівнем комерціалізації результатів наукової діяльності (близько 15 %); C – ЗВО з невеликим або відсутнім обсягом надходжень коштів від наукової діяльності (близько 5 %). Виявлено, що в аналізованому періоді спостерігалося поступове підвищення результатів підприємницької діяльності у науковій сфері 138 державних українських ЗВО: надходження ЗВО спочатку збільшилися від 363,688 млн грн у 2018 р. до 378,522 млн грн у 2019 р., а потім до 460,455 млн грн у 2020 р. Зауважено, що вагому частку цих доходів (≈79–80 %) становили надходження приблизно п’ятої частини ЗВО: 19,57 % у 2018 р., 18,84 % у 2019 р. і 23,19 % у 2020 р. Найбільш близьким до справдження принципу Парето 20/80, був 2018 р., коли співвідношення показників ЗВО і їхніх надходжень склало 20/79. Виявлено, що в 2018–2020 рр. 99 ЗВО України стабільно попадали в одні й ті ж групи за обсягом надходжень до спеціального фонду від наукової діяльності, 21 ЗВО підвищили свої позиції (як плавно, так і стрибкоподібно), 8 ЗВО – навпаки, знизили, а для 10 ЗВО тенденцій не виявлено. Рекомендовано зовнішнє та внутрішнє стимулювання комерціалізації наукової діяльності у ЗВО України.
Keywords: entrepreneurial activity; scientific sphere; higher education institutions of Ukraine; ABC-analysis; Pareto principle; monitoring; підприємницька діяльність; наукова сфера; заклади вищої освіти України; ABC-аналіз; принцип Парето; моніторинг